2009
DOI: 10.1093/toxsci/kfp006
|View full text |Cite
|
Sign up to set email alerts
|

Mode of Action Analysis for the Synthetic Pyrethroid Metofluthrin-Induced Rat Liver Tumors: Evidence for Hepatic CYP2B Induction and Hepatocyte Proliferation

Abstract: Two-year treatment with high doses of Metofluthrin produced hepatocellular tumors in both sexes of Wistar rats. To understand the mode of action (MOA) by which the tumors are produced, a series of studies examined the effects of Metofluthrin on hepatic microsomal cytochrome P450 (CYP) content, hepatocellular proliferation, hepatic gap junctional intercellular communication (GJIC), oxidative stress and apoptosis was conducted after one or two weeks of treatment. The global gene expression profile indicated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
43
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 41 publications
4
43
2
Order By: Relevance
“…These results suggest that patients suffering from Parkinson's disease given clinical doses of ORPH may not promote hepatocarcinogenesis, while the contribution of genotoxic potential of this compound should be addressed on the hepatocarcinogenicity. It has been shown that the chemicals that cause nuclear translocation of CAR and induce CYP2B have a liver tumor-promoting activity in rats (Deguchi et al, 2009). Chang (2009 described that the CAR protein is a receptor for xenobiotic ligands and an inducer of CYP2B1 in rats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results suggest that patients suffering from Parkinson's disease given clinical doses of ORPH may not promote hepatocarcinogenesis, while the contribution of genotoxic potential of this compound should be addressed on the hepatocarcinogenicity. It has been shown that the chemicals that cause nuclear translocation of CAR and induce CYP2B have a liver tumor-promoting activity in rats (Deguchi et al, 2009). Chang (2009 described that the CAR protein is a receptor for xenobiotic ligands and an inducer of CYP2B1 in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, CAR regulates not only the expression of various genes of Cyp2b but also of genes related to bioactivation, detoxification, and cell proliferation/ tumorigenesis (Chang, 2009), such as Cyclin D1, one of the genes activated by CAR and promoting hepatocellular growth (Ledda-Columbano et al, 2000). In addition, CAR is essential in the hepatic tumor-promotion mechanism (Deguchi et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, AH (4 and 20 mg/kg/d) also significantly increased the hepatic CYP2B activity. CYP2B induction is asso- ciated with liver tumor formation in rodents by activating nuclear receptors, particularly constitutive androstane receptor (CAR) (Deguchi et al, 2009;Lo et al, 2012). Therefore, betel-quid-induced liver cirrhosis and hepatocellular carcinoma might be associated with the induction of AH on rat hepatic 2B.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it can be deduced that Cyp2b10 was involved in PB-induced hepatocyte proliferation in male mice. Notably, the association of hepatocyte proliferation with CYP2B induction has also been observed for other CYP2B inducers, such as the environmental pollutant potassium perfluorooctanesulfonate and the synthetic pyrethroid metofluthrin (Deguchi et al, 2009;Elcombe et al, 2012). It remains to be determined whether CYP2B induction contributes to the hepatic hypertrophy induced by these other compounds.…”
Section: Cyp2b and Pb-induced Hepatocyte Proliferationmentioning
confidence: 96%